Study of Interfacial Properties of Anionic–Nonionic Surfactants Based on Succinic Acid Derivatives via Molecular Dynamics Simulations and the IGMH Method - Zhang, Wannian; Luo, Feng; Gao, Zhigang; Chi, Haizhu; Wang, Jinlong; Yu, Fang; He, Yu-Peng (Colloids and interfaces, 2024)
Surfactants are widely used in fields such as oil recovery and flotation. The properties and mechanisms of surfactants can be effectively studied using molecular dynamics (MD) simulations. Herein, the aggregation behavior of surfactants was studied at the oil–water interface by MD simulation, and the micro-morphology of surfactants was analyzed under a low concentration and saturated state at the oil–water interface, respectively. The visualization results of the MD simulation showed that DTOA was saturated at the oil–water interface at 120 surfactant molecules, whereas 160 surfactant molecules were required for BEMA. In addition, the effect of surfactant concentration on the interfacial thickness and hydrogen bond distribution was studied, with the inflection point of hydrogen bond distribution identified as a characteristic parameter for surfactant saturation at the oil–water interface. The aggregation behavior of their hydrophobic and hydrophilic chains at the oil–water interface was qualitatively assessed using order parameters. Finally, the aggregation state of surfactants in salt-containing systems was studied, and it was found that the surfactants could effectively adsorb magnesium ions and calcium ions at the oil–water interface. However, the curve of the number of hydrogen bonds varies greatly, with a possible reason being that BEMA has a different coordination manner with diverse metal ions. This study provides some original insights into both the theoretical study and practical application of anionic and nonionic surfactants.